1986
DOI: 10.1139/v86-083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diffusion coefficient of the zincate ion using a rotating disk electrode

Abstract: ELISABETE JORGE PESSINE, SILVIA M. L. AGOSTINHO, and HBLIO C. CHAGAS. Can. J. Chem. 64, 523 (1986). Using a rotating Hg-film disc electrode, the diffusion coefficient of the zincate ion in a 1-4 M aqueous solution of NaOH was measured. Experiments covered a temperature range from 25 to 40°C. The experimental results are in agreement with the predictions of the Stokes-Einstein theory for diffusivity. The obtained Stokes radii decrease with increasing alkali concentration, but the ratio D q / T is reasonably con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, charge screening alone is not sufficient to explain the high selectivity of Nafion for hydroxide over zincate. Although zincate is divalent while hydroxide is monovalent, zincate has a threefold larger hydrodynamic radius (0.34 nm, versus 0.11 nm for hydroxide), [ 36,37 ] resulting in a more diffuse charge. We believe that size‐based exclusion plays an equally important role and that the particularly high selectivity of NC‐Celgard stems from its lower wettability compared to bulk Nafion.…”
Section: Resultsmentioning
confidence: 99%
“…However, charge screening alone is not sufficient to explain the high selectivity of Nafion for hydroxide over zincate. Although zincate is divalent while hydroxide is monovalent, zincate has a threefold larger hydrodynamic radius (0.34 nm, versus 0.11 nm for hydroxide), [ 36,37 ] resulting in a more diffuse charge. We believe that size‐based exclusion plays an equally important role and that the particularly high selectivity of NC‐Celgard stems from its lower wettability compared to bulk Nafion.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, diffusion coefficient of zincate ions in 4 M NaOH (containing 2-10 mM zincate, at 25°C) is reported to be 3.10 × 10 À 6 cm 2 s À 1 . [33] At higher concentrations of both zincate and electrolyte, the reported diffusion coefficient value is significantly lower, i. e. 0.99 × 10 À 6 cm 2 s À 1 in 9 M KOH containing 1.21 M zincate and 0.14 × 10 À 6 cm 2 s À 1 in 11.2 M NaOH containing 1.43 M zincate. [34] Even though Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…These variations in diffusion coefficient value arise from presence of different combinations of zinc species coordinated to H 2 O, Cl − , and NH 3 in the mentioned environments. Moreover, diffusion coefficient of zincate ions in 4 M NaOH (containing 2–10 mM zincate, at 25 °C) is reported to be 3.10×10 −6 cm 2 s −1 [33] . At higher concentrations of both zincate and electrolyte, the reported diffusion coefficient value is significantly lower, i. e. 0.99×10 −6 cm 2 s −1 in 9 M KOH containing 1.21 M zincate and 0.14×10 −6 cm 2 s −1 in 11.2 M NaOH containing 1.43 M zincate [34]…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that the actual ionic conductivity may be dependent on the interplay between the effective mesh size and the hydrodynamic radius of charge conducting ions. When ZnO particles are dispersed into an alkaline solution, zincate complexes (Zn(OH) 4 2− ) are formed with a thin electric dipole layer of the solvent attached to the complex surface which influences the Brownian motion of the particles in the medium . Pessine et al.…”
Section: Resultsmentioning
confidence: 99%
“…Pessine et al. reported that the “solvodynamic radii” of Zn(OH) 4 2− calculated from the Stokes‐Einstein equation had a range of values from 0.35 to 0.41 nm . For hydroxide ions, Roobottom et al.…”
Section: Resultsmentioning
confidence: 99%